Argumentação no direito tributário - Frade, Eduardo Silveira (2024)
Law, as a linguistic object, is constantly reconstructed from speech acts issued by the subjects to whom it itself grants the competence to act in its formation. In addition to the norms issued, the arguments used also provide support for the reasons used by the agents, and must be considered in understanding the motivation that resulted in the decision of the established legal norm. In this sense, studying the argumentative rationality is imperative for understanding law, especially Tax Law, that becomes the object of this study, which also serves to list the order of classification and prevalence of arguments considered possible and, therefore, provide elements for a methodical approach of argumentation in this legal subsystem. To this end, a study of qualitative nature and deductive approach method is prepared, using indirect documentation as the main source of research that starts from a study of language and speech act theory as sources of law, understood as a system in which Tax Law is inserted, and that internal coherence must be maintained, but with a spirit of completeness, with interpretation and decision taken as essential instruments, from which the argumentation develops. Finally, a classification of arguments is created that serves to the study of decisions made in tax matters which permeates and provides elements for the construction of an argumentative theory in this legal subsystem